Prevalence of egg sensitization in Turkish infants based on skin prick test - (:unkn) unknown (ELSEVIER ESPANA SLU, 2008)
Aim: Egg allergy is one of the most frequent allergies in infants. The aim of this study was to determine the frequency of sensitization to egg in infants based on skin prick test results and to evaluate associated allergic conditions by questionnaire. Methods: All infants born between June 2001 and May 2002 were recalled to the hospital according to their dates of birth, and 1015 infants aged between 8-18 months were included in the study. An interview was conducted with each mother and a questionnaire requesting data on food allergy and other allergic diseases was completed during this interview. An egg skin prick test (whole egg) was applied to all infants. Results: Positive skin prick test results were recorded in 19 infants (1.87%). There was no difference between the prick test-positive and -negative groups with respect to any of the demographic characteristics investigated (gender, age, birth weight, egg consumption, age of introduction of egg and other solids, breastfeeding). No significant association was demonstrated between sensitization to egg and family history of allergy. Moreover, there was no association between sensitization to egg and occurrence of atopic dermatitis, recurrent wheezing, gastrointestinal symptoms and doctor diagnosis of asthma. Conclusion: The prevalence of egg sensitization based on skin prick test results has been found as 1.87% among Turkish infants in Istanbul. However, no significant relationship was found between allergic sensitization to egg and occurrence of allergic diseases in this study population.
Keywords: skin prick test; egg allergy; sensitization; infants; allergic diseases; ALLERGIC SENSITIZATION; FOOD CHALLENGES; DOUBLE-BLIND; CHILDREN; STANDARDIZATION; HISTORY; 1-YEAR; AGE